The agricultural development of Colombia - International Bank for Reconstruction and Development. [from old catalog] (Washington, 1956)
This publications is a report of a Mission organized by the International Bank for Reconstruction and Development at the request of the Government of the Republic of Colombia.
lje 03/07/17
Loans
Keywords: Agriculture; Agricultural development; Colombia